PERANCANGAN KOMIK SEJARAH PERANG PADRI DI SUMATERA BARAT ” THE HEROES OF PADRI” - PUJIAMA YUDHA, Hendra Afriwan, S.Sn., M.Sn., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Padri War comic tells the story of a war between brothers (Padri War). This story happened in West  Sumatra in 1803-1838. This historical event made in comic form, aims toincrease interest in reading the  youth to learn history through the medium of interest.Based on the problems, they invented the design of comics history "Padri War". Comics can be used as a  means to convey a moral message and understood directly by sipembacanya. One of the advantages  of comics is an interesting image visualization and easily understandable language.The design of the comic supported by theory (1) The theory of Padri War history, (2) learning theory, (3) The theory of motivation teenagers (4) The theory of design, (5) Theory Illustration and (6) The theory of  comics. This theory is used as a support in the completion of the design of comic history Padri War in West  Sumatra "The Heroes of Padri"In the design of this comic, the author uses the data in the form of a SWOT analysis. In the design of this  comic is supported by several media such as art books, note books, paper bags, posters, pens, stickers, X banner, support in the design of this comic.Keywords: West Sumatra, Padri War, History Comics.